An assessment of effect of government financial regulations on financial performance in Savings and Credit Cooperative Societies (SACCOs): A study of SACCOs in Kisii Central, Kenya - Otieno, Simeyo; Okengo, Benard Ochieng; Ojera, Patrick; Mamati, Francis (Centre for Promoting Ideas, USA, 2013)
Cooperatives are economic units by which members mobilize their financial resources through savings. It is estimated that this sector contributes about 20% to the gross Domestic Product. Although this sector is considered both economically and socially important, sectoral report indicates that nearly 2% of savings and Credit Cooperative Societies (SACCOs) collapse every year and about 6% of registered members withdraw their membership annually. Some SACCOs pay dividends which are as low as 3.5%. It is not clear why there is a deteriorating trend in most of the societies despite government’s financial regulations being in operation since 2004 that were meant to help SACCOs achieve sustainability through growth and financial stability. The objective of this study was to assess the effect of government’s financial regulations on financial performance in SACCOs in Kisii Central, Kenya. The study adopted descriptive research design and purposive sampling method. The research findings indicated that financial regulations contributed only 26.2% to the financial performance of SACCOs in Kisii Central.
Keywords: Financial regulation; SACCOs; Performance